Wintertime N2O5 uptake coefficients over the North China Plain - Wang, H. C.; Chen, X. R.; Lu, K. D.; Tan, Z. F.; Ma, XF; ZJ Wu; X. Li; Liu, Y. H.; Shang, D. J.; Y.S. Wu; L.M. Zeng; Hu, M.; et al. (Science Bulletin, 2020)
The heterogeneous hydrolysis of dinitrogen pentoxide (N2O5) plays an important role in regulating NOx. The N2O5 uptake coefficient, c(N2O5), was determined using an iterative box model that was constrained to observational data obtained in suburban Beijing from February to March 2016. The box model determined 2289 individual c(N2O5) values that varied from <0.001 to 0.02 with an average value of 0.0046 +/- 0.0039 (and a median value of 0.0032). We found the derived winter c(N2O5) values in Beijing were relatively low as compared to values reported in previous field studies conducted during winter in Hong Kong (average value of 0.014) and the eastern U.S. coast (median value of 0.0143). In our study, field evidence of the suppression of c(N2O5) values due to pNO3 content, organics and the enhancement by aerosol liquid water content (ALWC) is in line with previous laboratory study results. Low ALWC, high pNO3 content, and particle morphology (inorganic core with an organic shell) accounted for the low c (N2O5) values in the North China Plain (NCP) during wintertime. The field-derived c(N2O5) values are well reproduced by a revised parameterization method, which includes the aerosol size distribution, ALWC, nitrate and organic coating, suggesting the feasibility of comprehensive parameterization in the NCP during wintertime. (C) 2020 Science China Press. Published by Elsevier B.V. and Science China Press. All rights reserved.
Keywords: aerosol; ammonium-sulfate; clno2; gaseous n2o5; heterogeneous hydrolysis; liquid phase-separation; n2o5 uptake coefficient; nighttime chemistry; nitrate; nitrate pollution; particle-phase; reactive uptake; residual layer; winter air pollution